Approaches for end-of-life care in the field of gynecologic oncology: an exploratory study. Issue 4 (1st June 2004) - Ramondetta, L. M.; Tortolero-Luna, G.; Bodurka, D. C.; Sills, D.; Basen-Engquist, K.; Gano, J.; Levenback, C.
Abstract : We sought to explore the Society of Gynecologic Oncologists (SGO) members' opinions and decisions about end-of-life issues and incurable conditions. A survey was mailed to members of the SGO. Their responses were recorded on a Likert scale and entered into a database. The survey explored opinions, experiences, and decisions in managing terminally ill gynecologic oncology patients. Of 900 surveys, 327 were returned (response rate, 36%). Seventy-three percent were men, 89% were white, and 72% were of Christian denomination. Respondents believed that 97% of patients who are dying realize that they are dying but stated only 40% of these patients initiate conversations about end-of-life issues. In contrast, 92% of respondents stated that they initiate end-of-life discussions with patients. Ninety-two percent of respondents thought that the patients should be allowed to make end-of-life choices independently after the facts are given to them. However, 44% thought that it is important to influence the way information is presented, and 54% believe that the gynecologic oncologist (GO) controls the outcome of end-of-life discussions. Although the physicians' sex, race, religion, and age did not correlate with their treatment decisions, religion did correlate with less fear of death ( P = 0.011) and less discomfort when talking with patients about death ( P = 0.005). Fifty-four percent of respondents believed that the GO controls the outcome of end-of-life discussions, and 40% believe that their actions prolong the process of dying. Expanding our understanding of what motivates GOs to recommend continued treatment over palliation is important for preserving informed patient-motivated end-of-life decisions.